ANALISIS AERODINAMIKA PADA SIRIP LIPAT ROKET ARTILERI KALIBER 300 MM - Ahmad Novi Muslimin; Robertus Heru Triharjanto; Yayat Ruyat (POLITALA PRESS, 2023)
Aerodynamic analysis is an important part of the rocket design process. In this study, the analysis was carried out on the design of the 300 mm diametres artillery rocket fins. The rocket was developed to replace the TNI AD MLRS rocket, which is currently an imported product, so the geometry of the MLRS launch tube is a design limitation, and the rocket fins must be able to fold before launch. Aerodynamic analysis was carried out using the RASAero II flight speed Mach 2.0 application. Variations in the dimensions of the fins used in this study were: the length of the front and rear edges of the fins with variations in the size of 10, 30, and 50 mm, the thickness of the base of the fins with variations in the size of 5, 10 and 15 mm. The simulation results show that the folding fin size 50T5R has a drag force of 145 N and a lifting force of 1081 N, a fin with an optimal design. Based on natural frequency analysis, fins with sizes 10T5R, 10T10R, 30T5R, 30T10R, 50T5R, and 50T10R are fins with structural values safe from vibrational resonance.